A study of nitrogen dilution effect on the flammability limits of methane - Tengku Mohd Fadzli, Tengku Amin (2010)
Explosive/Flammability limits data are essential for a quantitative risk assessment of explosion hazard associated with the use of combustible gas. The present work is to obtain the fundamental explosive data for prevention of the hazards in the practical applications. Experiments have been conducted in a constant volume combustion bomb, and the fuel considered here is natural gas (NG). In this study, the nitrogen (N2) dilution effects on the flammability limits for pure hydrocarbons are explored. The effects of nitrogen on NG–air flammability limits have been investigated. By adding diluents nitrogen (N2) into NG–air mixture, the dilution effects on the flammability limits have been explored as well, and the results are plotted as functions of diluents ratio. From the results, it can be conclude that the range of flammability limits of methane is from 5 vol % until 18 vol %. The effect of nitrogen dilution on the upper flammability limit of methane observed with the reduction from 10 vol % to 30 vol % by increasing the vol % of nitrogen.